Pengaruh strategi know want learned berbantuan media kartu steam terhadap keterampilan membaca pemahaman peserta didik kelas 4 sekolah dasar - Nazihah, Inas Hanan; Rukayah, Rukayah; Yulisetiani, Septi (Didaktika Dwija Indria, 2024)
This research aims to determine the effect of using the KWL (Know, Want, Learned) strategy through STEAM card media on reading comprehension skills in grade 4 students in elementary schools. The research method used is a quantitative design with Nonequivalent Control Group Design. This research was conducted to assess whether the application of the KWL strategy through STEAM card media had a significant influence on students' reading comprehension skills. Apart from that, this research also aims to compare the average reading comprehension skills of students who use the KWL strategy via STEAM card media with those who do not. It is hoped that the results of this research will provide a better understanding of the KWL strategy in improving reading comprehension skills among grade 4 elementary school students. This research can also provide input for educators regarding the use of STEAM card media in the reading learning process. Thus, this research has important implications in the development of more effective learning methods in the field of reading comprehension skills at the basic education level.